Tesco targets China - Baack, Daniel W., (SAGE knowledge. Cases., 2016)
Tesco was founded in the United Kingdom in the early 20th century as a grocery retailer and has grown to become the third largest retailer in world. The company has a strong international presence, and this case study documents Tesco's strategic plans for further impact in the Chinese market.